Sensitization and chronic beryllium disease at a primary manufacturing facility, part 2: validation of historical exposures - Park, Ji Young; Virji, M. Abbas; Stefaniak, Aleksandr B.; Stanton, Marcia L.; Day, Gregory A.; Kent, Michael S.; Schuler, Christine R.; Kreiss, Kathleen (Scandinavian Journal of Work, Environment & Health, 2012)
' ' OBJECTIVE ': 'The aim of this study was to evaluate the validity of a job exposure matrix (JEM) constructed for the period 1994–1999. Historical exposure estimates (HEE) for the JEM were constructed for all job and year combinations by applying temporal factors reflecting annual change in area air measurements (1994–1998) to the personal baseline exposure estimates (BEE) collected in 1999. The JEM was generated for an epidemiologic study to examine quantitative exposure–response relationships with sensitization and chronic beryllium disease. ' ' METHODS ': 'The validity of the BEE and HEE was evaluated by comparing them with a validation dataset of independently collected personal beryllium exposure measurements from 1999 and 1994–1998, respectively. Agreement between the JEM and validation data was assessed using relative bias and concordance correlation coefficients (CCC). ' ' RESULTS ': 'The BEE and HEE overestimated the measured exposures in their respective validation datasets by 8% and 6%, respectively. The CCC reflecting the deviation of the fitted line from the concordance line, showed good agreement for both BEE (CCC=0.80) and HEE (CCC=0.72). Proportional difference did not change with exposure levels or by process area and year. Overall, the agreement between the JEM and validation estimates (from combined HEE and BEE) was high (CCC=0.77). ' ' CONCLUSIONS ': 'This study demonstrated that the reconstructed beryllium exposures at a manufacturing facility were reliable and can be used in epidemiologic studies.
Keywords: agreement; beryllium; chronic beryllium disease; exposure; exposure reconstruction; historical exposure; job exposure matrix; manufacturing; sensitization; total exposure; validation